2019
DOI: 10.1088/1757-899x/662/3/032056
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Application for Small Medium Enterprises

Abstract: This paper aims to show the benefits of accounting applications for small and medium business enterprises (SMEs), as a means to shape entrepreneurs in managing business financial data, easily and safely because making financial data manually is a way that carries a high risk. The method used was a method of description that is by reviewing research that has been made before. The results of this study indicate the use of accounting applications that helps entrepreneurs in processing financial data easily, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Dalam sub tema ini, penelitian berfokus pada pembuatan, perancangan atau penerapan aplikasi akuntansi berbasis online di instansi, perusahaan atau Usaha Mikro Kecil dan Menengah (UMKM). Peneliti yang membahas sub tema ini diantaranya Aini, Rahardja, Arribathi, & Santoso (2019), Rahardja, Aini, & Hardini (2018), Arief (2013), Kirana & Sitanggang (2019), Wibawa et al (2019), Suhayati & Riandani (2019), dan Arifin, Jeong, & Ock (2014). Kedua, evaluasi, monitoring atau mengukur efektivitas.…”
Section: Penelitian Cloud Accounting DI Indonesiaunclassified
“…Dalam sub tema ini, penelitian berfokus pada pembuatan, perancangan atau penerapan aplikasi akuntansi berbasis online di instansi, perusahaan atau Usaha Mikro Kecil dan Menengah (UMKM). Peneliti yang membahas sub tema ini diantaranya Aini, Rahardja, Arribathi, & Santoso (2019), Rahardja, Aini, & Hardini (2018), Arief (2013), Kirana & Sitanggang (2019), Wibawa et al (2019), Suhayati & Riandani (2019), dan Arifin, Jeong, & Ock (2014). Kedua, evaluasi, monitoring atau mengukur efektivitas.…”
Section: Penelitian Cloud Accounting DI Indonesiaunclassified
“…Untuk membantu pemilik usaha dalam melakukan pencatatan keuangan, sejumlah upaya mulai dari konvensional sampai modern seperti pembuatan dan pemanfaatan aplikasi akuntansi (accounting application) telah dilakukan untuk membantu kemudahan pembuatan laporan keuangan (Suhayati dan Riandani, 2019). Namun penggunaan aplikasi modern akan tepat digunakan jika pelaku bisnis UMKM sudah mengerti dasardasar dari pelaporan keuangan, terlebih lagi, tidak semua pelaku bisnis UMKM mampu menggunakan teknologi tersebut.…”
Section: Pendahuluanunclassified
“…There are several considerations in using the software to support the accounting work process for faster and easier use which are a valid level of security for each user, the ability to explore all reports to the excel program without going through the export and import process, which will make it difficult to display the comparative financial statements (Suhayati, E., & Riandani, I. 2019 This study identified the previous research that operationally accounting information systems use processes to convert inputs into outputs to achieve the overall system objectives.…”
Section: Introductionmentioning
confidence: 99%